“Eugenics talk” and the language of bioethics - Wilkinson, S (BMJ Publishing Group, 2008)
In bioethical discussions of preimplantation genetic diagnosis and prenatal screening, accusations of eugenics are commonplace, as are counter-claims that talk of eugenics is misleading and unhelpful. This paper asks whether “eugenics talk”, in this context, is legitimate and useful or something to be avoided. It also looks at the extent to which this linguistic question can be answered without first answering relevant substantive moral questions. Its main conclusion is that the best and most non-partisan argument for avoiding eugenics talk is the Autonomy Argument. According to this, eugenics talk per se is not wrong, but there is something wrong with using its emotive power as a means of circumventing people’s critical–rational faculties. The Autonomy Argument does not, however, tell against eugenics talk when such language is used to shock people into critical–rational thought. These conclusions do not depend on unique features of eugenics: similar considerations apply to emotive language throughout bioethics.